Metabolized-water breeding diseases in urban India: Socio-spatiality of water problems and health burden in Ahmedabad - Saravanan V. Subramanian; Dileep Mavalankar; Suhas P. Kulkarni; Sven Nussbaum; Martin Weigelt (University of Bonn, Center for Development Research (ZEF), 2014)
Studies on urban metabolism have provided important insights in the material and socio political issues associated with the flow. However, there is dearth of studies that reveal how infrastructure as a hybrid of social and material construct facilitates disease emergence. The paper brings together urban metabolism, political ecology and anthropological studies to examine how the material flow of water is socially constructed and reconstructed through everyday water problems and its health burden in Ahmedabad city, India. The article geo-references the water problems and occurrence of diseases and through interviews documents the socio-spatial characteristics of water problems and health burden in two case study wards. The paper provides a situated understanding of the everyday practices that exposes the water infrastructure through leakages, reveals the citizens desire for better water quality and struggle to gain access to water using diverse 'pressure' tactics. It is this social-material construct of infrastructure that gives structure and coherence to urban space, which spatially coincides with the occurrence of diseases. The analysis reveals the socio-political drivers of the water problems, spatial inequity in water access, and identify potential hypothesis of the hot-spots of disease emergences. Attempts to bring about a desired change have to be collective and incremental that takes into consideration the diffuse interplay of power by diverse actors in managing the flow of water. The methodology offers a way forward for researchers and development agencies to improve the surveillance and monitoring of water infrastructure and public health. By bringing 'place-based' and 'people-based' approach, the analysis charts out avenues for incorporating the socio-spatiality of the everyday problems within the field of urban metabolism for improving resource use efficiencies in cities of rapidly growing economies.
Keywords: 330; Urban metabolism; techno-politics; institutional analysis; spatial analysis; public health; India